Highly efficient broadband white-light emission in two-dimensional semi-conductive hybrid lead chlorides. Issue 39 (15th September 2022) - Wang, Yuyin; Sun, Chen; Su, Bin; Li, Xianfeng; Meng, Xiangxi; Lou, Huiru; Cheng, Ziwen; Wang, Ying; Lin, Guoming
Abstract : Compound [DTHPE]Pb4 Cl10 exhibits bright wide-band white-light emission featuring a high PLQE of 8.86% with high anti-water stability and excellent photoelectric response, which makes it a promising candidate in the multifunctional photoelectronic field. Abstract : White-light emission (WLE) materials based on organic–inorganic hybrid lead halides have drawn considerable attention because of their applications in light-emission equipment. Despite considerable efforts, there is still a lack of two-dimensional (2D) lead-chlorine white-light emitting halides with high photoluminescence quantum efficiency (PLQE). Herein, we report the preparation of a new 2D layered hybrid halide, [DTHPE]Pb4 Cl10, which exhibits bright wide-band WLE, a high PLQE of 8.86% and high anti-water stability. To the best of our knowledge, the PLQE of [DTHPE]Pb4 Cl10 exceeds that of most 2D lead chlorides. Furthermore, the emission intensity is unchanged even after continuous immersion in water for 7 days. Photoluminescence measurements indicate that the WLE originates from self-trapped excitons. [DTHPE]Pb4 Cl10 is a promising visible-blind UV hybrid halide owing to its excellent photoelectric response. [DTHPE]Pb4 Cl10 is an effective white-light emitting material for display applications. The coexistence of a high performance visible-blind UV response and high efficiency white-light emission provides attractive possibilities for potential applications in the multifunctional photoelectronic field.